2022
DOI: 10.3390/biom12101350
|View full text |Cite
|
Sign up to set email alerts
|

Teenage-Onset Colorectal Cancers in a Digenic Cancer Predisposition Syndrome Provide Clues for the Interaction between Mismatch Repair and Polymerase δ Proofreading Deficiency in Tumorigenesis

Abstract: Colorectal cancer (CRC) in adolescents and young adults (AYA) is very rare. Known predisposition syndromes include Lynch syndrome (LS) due to highly penetrant MLH1 and MSH2 alleles, familial adenomatous polyposis (FAP), constitutional mismatch-repair deficiency (CMMRD), and polymerase proofreading-associated polyposis (PPAP). Yet, 60% of AYA-CRC cases remain unexplained. In two teenage siblings with multiple adenomas and CRC, we identified a maternally inherited heterozygous PMS2 exon 12 deletion, NM_000535.7:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In a similar reported case, in which a patient with a POLE frameshift germline variant presented mainly somatic MMRd-associated signatures, it could not be concluded whether the identified variant increased colorectal cancer predisposition ( Yamaguchi et al, 2019 ; Mur et al, 2020b ; Yamaguchi and Furukawa, 2020 ). It has also been speculated that POLD1 pathogenic variants cause hypermutation only with concurrent MMRd, with the latter as an early event ( Schamschula et al, 2022 ). However, it should also be considered whether mutational signatures associated with POLD1 exonuclease domain malfunction could differ from those arising from loss-of-function alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar reported case, in which a patient with a POLE frameshift germline variant presented mainly somatic MMRd-associated signatures, it could not be concluded whether the identified variant increased colorectal cancer predisposition ( Yamaguchi et al, 2019 ; Mur et al, 2020b ; Yamaguchi and Furukawa, 2020 ). It has also been speculated that POLD1 pathogenic variants cause hypermutation only with concurrent MMRd, with the latter as an early event ( Schamschula et al, 2022 ). However, it should also be considered whether mutational signatures associated with POLD1 exonuclease domain malfunction could differ from those arising from loss-of-function alterations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that a solitary heterozygous POLD1 mutation in the exonuclease domain without concurrent mutations in other repair systems causes only a modest increase in the mutation rate [ 95 ]. In addition, Schamschula et al suggested that POLD1 -mutated cancers acquire the ultra-high TMB only with concurrent mismatch repair deficiency [ 66 ]. It is hypothesized that there are no cancers with an exclusive heterozygous POLD1 mutation and only a complete loss of the two POLD1 alleles can lead to cancer [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the association of POLE / POLD1 mutation with MSI status in various cancers have shown ambiguous results. Although cancers harboring POLD1 mutation are believed to be primarily microsatellite stable, some of them may display an MSI-H phenotype [ 55 , 63 , 64 , 65 , 66 , 67 , 68 ]. Wang et al’s study on a cohort of almost 50,000 patients with different solid cancer types assessed the impact of POLE / POLD1 mutations on immunotherapy outcomes [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The facts that path_PMS2 carriers do not develop cancer as frequently as other path_MMR carriers and members of the same family affected by the same path_PMS2 variant also demonstrate a wide range of age for cancer-onset offer potential evidence of digenic inheritance among this group of carriers. Indeed, a very recent case-report described two teenage siblings with multiple adenomas and CRC with a maternally inherited path_PMS2 variant and a paternally inherited path_POLD1 variant ( 93 ). Interestingly, molecular studies of the tumours revealed an ultra-mutated tumour phenotype with mutational signatures of both PMS2 and POLD1 , suggesting that these factors interacted to cause the relatively severe clinical phenotype in these cases.…”
Section: Futurementioning
confidence: 99%